(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Maria-Ioana Oancea explores the myth of Orpheus in Mircea Eliade’s novella In curte la Dionis, linking it to C.G. Jung’s theories on psychological transference. The study analyzes the ambiguous relationship between the savior and the saved, where memory loss represents a descent into a personal Hell. Ultimately, salvation requires mutual trust and a shared emotional awakening. Through art and love, the characters transcend their isolation, achieving a spiritual unification between the conscious and the subconscious. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.